Delayed Justice in Protecting Emergency Medical Workers - Mashdurohatun, Anis; I Made Dwi Jayantara; Rudi Iskandar; Suroto; Ahmed Rabie (Lembaga Contrarius Indonesia, 2025)
Despite recent legal provisions to protect emergency medical personnel in Indonesia, many still face criminal, civil, or administrative sanctions, revealing gaps in the current law’s effectiveness this study uniquely analyzes and proposes reconstructive reforms based on justice principles. This study employs a descriptive-analytical method within a constructivist paradigm and socio-legal approach, integrating Islamic and Pancasila justice as grand theories, legal systems theory as a middle-range framework, and theories of legal protection and progressive law as applied perspectives to comprehensively analyze emergency medical personnel’s legal protection. The findings reveal several key weaknesses. First, at the substantive level, vague and ambiguous legal norms result in inconsistent court decisions regarding the liability of medical personnel during emergency services. Second, at the structural level, disciplinary and ethical institutions lack assertiveness and clarity in enforcing professional accountability. Third, at the cultural level, crucial values such as patient safety, autonomy, and a culture of apology have not been fully embedded in medical practice. To address these problems, the study proposes a reconstruction of the legal framework by promoting centralized responsibility, expanding immunity protections for emergency actions, extending procedural time limits, and recognizing the role of unified professional organizations. These reforms aim to ensure effective and just legal protection for medical personnel.